Remain 5 star achievement, UMP focuses on improving higher education quality - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 4 January 2022 - Universiti Malaysia Pahang (UMP) will continue to strengthen its efforts in advancing and expanding higher education by focusing on higher level education and Technical and Vocational Training (TVET)